Development of Mobile Learning in Learning Media to Improve Digital Literacy and Student Learning Outcomes in Physics Subjects: Systematic Literature Review - Rafi Eka Wijaya; Mustaji Mustaji; Hari Sugiharto (Budapest International Research and Critics University, 2021)
This study aims to analyze the development of mobile learning in learning media to improve digital literacy and student learning outcomes in physics subjects. The method used in writing this systematic literature review is to search for the literature using a database on Google Scholar. The results of the study show that the use of mobile learning in student learning can be used as a learning support tool, media and learning resource and can be applied at the student level. The benefits of using mobile learning in learning are that it can facilitate the teaching and learning process both in the classroom and outside the classroom, attract students' attention and can generate enthusiasm and motivation in learning so that the material being delivered can be conveyed properly and can be understood by students, besides another benefit of using mobile learning is that it can support students towards independent learning. The development of mobile learning as a learning medium has been carried out by several researchers, who develop mobile learning. The results of the development carried out indicate that the media developed is more likely to focus on the teaching material only. Mobile learning developed is focused as a means of practicing working on questions that can provide various types of questions that are varied and challenging.